2010
DOI: 10.1254/jphs.10131fp
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Embolic Model of Cerebral Infarction and Evaluation of Stachybotrys microspora Triprenyl Phenol-7 (SMTP-7), a Novel Fungal Triprenyl Phenol Metabolite

Abstract: Abstract. The aim of the present study was to establish a novel embolic model of cerebral infarction and to evaluate the effect of Stachybotrys microspora triprenyl phenol-7 (SMTP-7), a novel fungal triprenyl phenol metabolite. Thrombotic occlusion was induced by transfer of acetic acid-induced embolus into the brain. The regional cerebral blood flow was measured by a laser Doppler flowmeter to check the ischemic condition. Infarction area was assessed by 2% 2,3,5-triphenyltetrazolium chloride (TTC) staining. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
1
43
1
Order By: Relevance
“…DISCUSSION SMTP-7 has a plasminogen modulation activity that leads to a thrombolytic enhancement as observed in several animal models (14,16,20). SMTP-7 effectively treats thrombotic and embolic stroke models (17,18,20), and the involvement of an additional mechanism that leads to anti-inflammation has been suggested (16,18,19,21). In the present study we observed the SMTP anti-inflammatory action that is independent of the plasminogen modulation activity.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…DISCUSSION SMTP-7 has a plasminogen modulation activity that leads to a thrombolytic enhancement as observed in several animal models (14,16,20). SMTP-7 effectively treats thrombotic and embolic stroke models (17,18,20), and the involvement of an additional mechanism that leads to anti-inflammation has been suggested (16,18,19,21). In the present study we observed the SMTP anti-inflammatory action that is independent of the plasminogen modulation activity.…”
supporting
confidence: 72%
“…1A), one of the SMTP family compounds with profound biological activities, enhances plasminogen activation by modulating plasminogen conformation (10,(13)(14)(15). SMTP-7 thus promotes plasmin formation and clot clearance in vivo (14,16), and it has been used to treat thrombotic and embolic strokes in experimental models in rodents and nonhuman primates (17)(18)(19)(20). Unexpectedly, SMTP-7 was demonstrated to reduce hemorrhagic transformation and to have a wide therapeutic time window (17,18,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5-7 SMTP-7, one of the most potent congeners, is effective in treating thrombotic stroke. [8][9][10][11] The SMTP molecule consists of a tricyclic g-lactam moiety, a geranylmethyl group, and an N-linked side chain. Our previous studies identified 26 SMTP congeners, most of which differ in the side chain.…”
mentioning
confidence: 99%